Enhancing College English Teaching with Sports Psychology: A Hybrid Flipped Approach - Yiwen Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study aims to explore the effectiveness of blended flipped college English teaching based on sports psychological intervention. Flipped classroom is a student-centered teaching method, which emphasizes students' independent learning outside the classroom and in-depth discussion and practice in the classroom. Sports psychological intervention is an intervention method that promotes students' physical and mental health and learning performance through sports activities and training. With the help of MOOC concept and technology, the author designs a new hybrid college English teaching model based on Flipped classroom with the core concept of "interaction and collaboration", and applies it to teaching practice. The research results indicate that, this teaching mode enhances students' interest in learning, cultivates their autonomous learning ability, enhances the spirit of unity and cooperation among students, improves their innovation awareness and critical thinking ability, and has a significant teaching effect.